‘Kapitalisten’ and ‘Prywaciarze’. A Comparison of Nationalisation Campaigns in the GDR and Poland - Flade, Falk; Kamosiński, Sławomir (Studia Historiae Oeconomicae, 2021)
This paper compares nationalisation campaigns in the German Democratic Republic and socialist Poland, with particular focus on industry. It is based on secondary literature as well as material from both the German and Polish statistical offices. The main finding is a surprising lack of simultaneity in the nationalisation campaigns in the two countries, which possibly had a significant impact on the course of economic transformation in East Germany and in Poland.